1997
DOI: 10.1002/(sici)1097-4601(1997)29:12<915::aid-kin3>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reaction: H+HI?H2+I at 298 K and very low pressures

Abstract: The reaction was studied at 298 K and millitorr pressures em-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The optimization of a kinetic model of the pyrolysis of ethyl iodide was carried out on the basis of reflected shock wave experiments with H‐ARAS and I‐ARAS detection , and rate coefficient measurements from Michael et al , and Vasileiadis and Benson . Arrhenius parameters A and E of the following four reactions were determined in the temperature range 950–1400 K and a pressure range of 1–2 bar: (R1): C 2 H 5 I → C 2 H 5 + I; (R3): C 2 H 5 I → C 2 H 4 + HI; (R4): H + HI → H 2 + I; (R5): C 2 H 5 I + H →C 2 H 5 + HI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The optimization of a kinetic model of the pyrolysis of ethyl iodide was carried out on the basis of reflected shock wave experiments with H‐ARAS and I‐ARAS detection , and rate coefficient measurements from Michael et al , and Vasileiadis and Benson . Arrhenius parameters A and E of the following four reactions were determined in the temperature range 950–1400 K and a pressure range of 1–2 bar: (R1): C 2 H 5 I → C 2 H 5 + I; (R3): C 2 H 5 I → C 2 H 4 + HI; (R4): H + HI → H 2 + I; (R5): C 2 H 5 I + H →C 2 H 5 + HI.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty limits are indicated only in the temperature range of our measurements (950-1400 K). The numbered thin lines show previously published rate coefficients: (1) Kumaran et al [20] (p = 0.1-0.7 bar), (2) Yang and Conway [25] (p = 0.02 bar), (3) Shilov and Sabirova [26], (4) Ogg [27] (p = 0.2 bar), (5) Sullivan [17] (p = 0.2 bar), (6) Yang and Tranter [19] (p = 0.07-0.16 bar; plotted values are the high-pressure extrapolation), (7) Benson and Bose [28] (p = 0.08-0.25 bar), (8) Butler and Polanyi [29] (p = 0.002-0.017 bar), (9) Michael et al [11], (10) Vasileiadis and Benson [13], (11) Baulch et al [9], (12) Lorenz et al [16], (13) Sullivan [30], and (14) Yuan et al [21] Arrhenius parameters showed a significantly better agreement with the experimental results compared to the simulations performed with the initial parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations